1970
DOI: 10.1677/joe.0.0470321
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Steroid Biosynthesis in the Intact Graafian Follicle of Mares in Oestrus

Abstract: Two mares were operated on during oestrus; in the first animal a mixture of [16-3H]pregnenolone and [4-14C]androstenedione was injected into the largest Graafian follicle; in the second animal, [4-14C]pregnenolone and [7-3H]androstenedione were injected into the follicle. By cannulating the ovarian veins it was possible to measure the rate of transfer of radioactivity from the follicular fluid into the ovarian vein. This ranged from 3 to 9 % of the injected dose per hour. At the end of each experiment, 45-52 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 22 publications
(28 reference statements)
5
26
0
Order By: Relevance
“…Hormonal concentrations in the follicular fluid were not measured in the present study. Intrafollicular steroids probably diffuse slowly out of follicular fluid into the ovarian vein (YoungLai & Short, 1970). This seems to be the case for elephants; 2 of the cows had only a single follicle each and the other 2 cows had 2 and 3 CL with small volumes (200 + 0-50cm3) and follicles present in the ovaries, with high plasma progesterone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal concentrations in the follicular fluid were not measured in the present study. Intrafollicular steroids probably diffuse slowly out of follicular fluid into the ovarian vein (YoungLai & Short, 1970). This seems to be the case for elephants; 2 of the cows had only a single follicle each and the other 2 cows had 2 and 3 CL with small volumes (200 + 0-50cm3) and follicles present in the ovaries, with high plasma progesterone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that the ability of the follicular fluid to maintain an estradiol gradient was lost following treatment with trypsin, suggesting that it is maintained by the action of a binding protein. The average and standard error represent three separate experiments with a significant but slower leakage to the serum could not be the explanation [5].…”
Section: Discussionmentioning
confidence: 95%
“…However, the rate of release of steroids from the follicle is very slow. Younglai et al established that the hourly transfer of estrogen from the follicle to the circulation is only 3-9 % [5]. Interestingly, despite the significant concentration difference of estradiol and slow rate of release, the concentration of the known estrogenbinding proteins SHBG and albumin is similar to or even lower in the FF in comparison to the serum [4].…”
Section: Introductionmentioning
confidence: 99%
“…luteal cells, probably indicates that in the rabbit ovary both these enzymes may be induced under the action of LH. However, it is pertinent to mention here that there exists considerable species variation with regard to the distribution/ sites of enzyme activity in the Graafian folli cles and corpora lutea of the mammalian ovary [references in Dorrington, 1977], While in the rat and hamster the granulosa cells show high A5-3(5-HSD and are consid ered to be the principal source of estrogen [Dorrington et al, 1975;Makris and Ryan, 1977], in the rabbit, mare, sheep and mon key the thecal cells are regarded as impor tant sites of synthesis [ Younglai and Short, 1970;Hay and Moor, 1975;Charming and Coudert, 1976;Watson and Dodson, 1976]. Further, in the rabbit, known to ovulate in response to coitus, Sawyer [1959] showed that estrogen priming alone induces ovula tion, and mating usually initiates a sharp rise in LH concentration within 15 min which peaks on the average during the 2nd hour, then declines gradually to basal levels by 4-5 h [Scaramuzzi et al, 1972;Dufy-Barbe et al, 1973b;Goodman and Neil, 1976], Therefore, the presence of high peroxidase and A5-3|3-HSD mainly in the luteal cells rather than in granulosa cells suggests that these enzymes induced after coitus under the action of LH may regulate together the biosynthetic machinery controlling luteal steroidogenesis during pregnancy.…”
Section: Discussionmentioning
confidence: 99%